Modelling and Trajectory Tracking of Wheeled Mobile Robots. (2016) - Leena, N.; Saju, K.K.
Abstract: Differential drive mobile robots are widely used due to their simplicity, easiness of control and flexibility. This paper discuss a detailed modeling of a differential drive robot taking into account the kinematics, actuator dynamics and rolling resistances of the wheels. Controllers have been designed for smooth trajectory tracking. Different trajectories similar to real life scenarios have been created and the model and control algorithm are seen to give accurate trajectory tracking.